Women loving stories and a play - Cruz, Jhoanna Lynn B. (Manila Anvil Pub., 2010)
"This is a collection of lesbian stories (and a full-length play); of characters who are in transit: running away or coming home."--Preface.
The girl has turned into a woman and other rites of passage -- Liway -- Comadrona -- How Manong Victor brought home his baket -- Landing -- Cielo -- Christmas lights -- Lost and found -- Halataka, Ms. D!
Keywords: Short stories, Philippine (English); Lesbians -- Fiction